Multilingual Adaptive Search for Digital Libraries - LAWLESS, SEAMUS; GHORAB, MOHAMMED RAMI ELHUSSEIN; O'CONNOR, ALEXANDER; ZHOU, DONG; WADE, VINCENT (LNCS, 2011)
We describe a framework for Adaptive Multilingual Information Retrieval (AMIR) which allows multilingual resource discovery and delivery using on-the-fly machine translation of documents and queries. Result documents are presented to the user in a contextualised manner. Challenges and affordances of both adaptive and multilingual IR, with a particular focus on digital libraries, are detailed. The framework components are motivated by a series of results from experiments on query logs and documents from The European Library. We conclude that factoring adaptivity and multilinguality aspects into the search process can enhance the user?s experience with online digital libraries.
15th International Conference on Theory and Practice in Digital Libraries (TPDL 2011)
PUBLISHED
Humboldt-Universitat zu Berlin, Berlin, Germany
Keywords: Computer Science and Engineering; Multilingual Adaptive Search; Digital Libraries; Digital Humanities; Intelligent Content & Communications